Prevalence and risk factors associated with chronic kidney disease in an adult population from southern China - Chen, Wei (Oxford University Press, 2009)
Background. Population-based studies evaluating the prevalence of kidney damage in different communities have been limited in developing countries. We conducted a population-based screening study in the southern Chinese city of Guangzhou that aimed to identify the prevalence and associated risk factors of chronic kidney disease (CKD) in southern Chinese populations. Methods. We interviewed 6311 residents (>20 years) from six districts of Guangzhou from July 2006 to June 2007 and tested for haematuria, albuminuria and reduced renal function. Associations between age, gender, smoking, diabetes mellitus, hypertension, hyperuricaemia and kidney damage were examined. Results. There were 6311 subjects enrolled in this study. After adjustment for age and gender, the prevalence of albuminuria, haematuria and reduced estimated glomerular filtration rate (eGFR) was 6.6% [95% confidence interval (CI): 5.5–7.6%], 3.8% (95% CI: 3.4%, 4.3%) and 3.2% (95% CI: 2.4%, 3.3%), respectively. Approximately 12.1% (95% CI: 11.3%, 12.9%) of the sample population had at least one indicator of kidney damage. Age, diabetes mellitus, hypertension, central obesity, hyperlipidaemia and use of nephrotoxic medications were independently associated with albuminuria; hyperuricaemia, age, gender, hypertension and use of nephrotoxic medications were independently associated with reduced eGFR, and female gender was independently associated with haematuria. Conclusions. In the general adult population from southern China, 12.1% has either proteinuria, haematuria and/or reduced eGFR, indicating the presence of kidney damage, with an awareness of only 9.6%. The high prevalence and low awareness of CKD in this population suggest an urgent need for CKD prevention programmes in China.